FAKTOR YANG BERPENGARUH TERHADAP KEMATIAN NEONATAL DINI AKIBAT ASFIKSIA DI KABUPATEN TIMOR TENGAH SELATAN - Bernadeta Erni; Filpin Luciami A Haning (PT. Hasba Edukasi Mandiri, 2025)
The infant mortality rate is also an important indicator to reflect the state of health status in a society, progress in the field of prevention and eradication of various diseases that cause death will be clearly reflected by the decline in the level of IMR. Thus the infant mortality rate is a sensitive measure of all intervention efforts made by the government, especially in the health sector. The purpose of this study was to find out and analyze what factors had the most influence on early neonatal deaths due to asphyxia in Timor Tengah Selatan Regency in 2025. The design of this study used a case-control research design with a retrospective study approach. The population in this study was divided into 2, namely the case population were all live births that experienced asphyxia and died in early Neonatal and the control population in this study were all live births who had asphyxia and did not die in the 2024 period in the work area of the Health Service. South Central Timor Regency (TTS). The sample size in this study was taken using a total sampling technique, where the entire population was used as the research sample, namely as many as 26 case samples, with a sample size comparison between cases and controls was 1:1, so the total sample size was 52 samples. The results showed that there was an effect of gestational interval (95% CI = 3.20-47.834 p-value = 0.000), history of premature (95% CI = 1.836-20.315 p-value = 0.003) and asphyxia (95% CI = 4.509- 74.539 p-value = 0.000) on Early Neonatal Death in Timor Tengah Selatan Regency (TTS). There was no effect of parity on gestational age (p-value=0.213), anemia (p-value=0.432), Long Parturition (p- value=0.201) and ANC visits (p-value=0.211 on Early Neonatal Mortality in Timor Tengah Selatan Regency (TTS) The most dominant variable and the most influential on the incidence of Early Neonatal mortality is the Asphyxia variable.